External Parasites of Poultry - Phillip E. Kaufman; Philip G. Koehler; Jerry F. Butler (EDIS, 2008)
Revised! ENY-290, a 12-page fact sheet by P. E. Kaufman, P. G. Koehler, and J. F. Butler, describes several external parasites of poultry in Florida, insecticide resistance, and control. Includes tables of pesticides registered in Florida for poultry pests and for insects in poultry houses. Published by the UF Department of Entomology and Nematology, November 2007.